1995
DOI: 10.1099/0022-1317-76-2-425
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal phosphorylation of human respiratory syncytial virus P protein occurs mainly at serine residue 232

Abstract: To determine which human respiratory syncytial virus (HRSV) P protein serine residues are modified by cellular protein kinase(s), several mutated versions of P protein were expressed in the absence of other viral proteins. Mutations at serines 232 or 232 and 237 drastically reduced the extent of phosphorylation P protein in vivo. Serine 232 is the main site of modification and is also essential for in vitro phosphorylation by casein kinase II. Additional in vivo phosphorylation was also detected in the region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 18 publications
4
31
0
2
Order By: Relevance
“…3E). Our data showed that N mono copurified with GST-P and GST-P but not with GST-P [1][2][3][4][5][6][7][8][9][10], GST-P [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], GST-P , or GST-P . These results revealed that an N mono -specific binding site is located between amino acids 1 and 29 of P. It is noteworthy that residues 1 to 10, if not sufficient to interact with N mono , are required for the interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3E). Our data showed that N mono copurified with GST-P and GST-P but not with GST-P [1][2][3][4][5][6][7][8][9][10], GST-P [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], GST-P , or GST-P . These results revealed that an N mono -specific binding site is located between amino acids 1 and 29 of P. It is noteworthy that residues 1 to 10, if not sufficient to interact with N mono , are required for the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The RSV P protein is composed of 241 amino acids and constitutes the shortest P protein among paramyxoviruses. Human RSV P (strain Long) is phosphorylated mainly at S232 (7,8), although other minor phosphorylation sites have been identified (S30, S39, S45, T46, S54, T108, S116, S117, S119, S237) (9,10). The precise role of phosphorylation for P activity remains unclear, since (i) unphosphorylated P is competent for oligomerization and binding to N-RNA (11,12) and (ii) substitution of all the phosphorylated residues has little effect on viral transcription and replication (13,14).…”
mentioning
confidence: 99%
“…Phosphorylation is mediated by the cellular casein kinase II (8, 33) on two clusters of serines: 116, 117, and 119 in the central region and 232 and 237 in the C-terminal region (26,27,31,33). Approximately 80% of P protein phosphorylation is localized to Ser-232, and the remaining 20% is distributed among Ser-116, -117, -119, and -237.…”
mentioning
confidence: 99%
“…In RSV P protein, two clusters of phosphorylation sites (amino acid residues 116, 117, and 119 and residues 232 and 237) have been identified (5,9,21,24,34). Phosphorylation of S232 was proposed to regulate RSV transcription; however, that study was based on in vitro assays (33).…”
mentioning
confidence: 99%